A Narrative Perspective on Entrepreneurial Opportunities - Garud, Raghu; Giuliani, Antonio Paco (Academy of Management Review, 2013)
There continues to be considerable interest in entrepreneurial processes, as evidenced in recent reflection pieces in AMR (Shane, 2012; Venkataraman, Sarasvathy, Dew, & Forster, 2012). Of particular interest are questions about the sources of entrepreneurial opportunities. For instance, are entrepreneurial opportunities a result of a process of discovery or one of creation? Should we locate agency in specific individuals, or should we conceptualize entrepreneurs as part of a larger process where agency is distributed and emergent? To address these questions, Shane (2012) distinguishes between "opportunities" and "business ideas" to account for both entrepreneurial failures and successes and to advance a notion of entrepreneurial agency emerging at the nexus of individuals and opportunities. Opportunities, for Shane, are objectively given, ones that individuals can seize by generating business ideas that are interpretations "of how to recombine resources in a way that allows pursuit of that opportunity" (Shane, 2012: 15). Venkataraman et al. (2012) take a different route, embracing Simon's (1996) sciences of the artificial. Building on Davidson's (2001) "tripod" consisting of interactions among objective, subjective, and intersubjective, the authors conceptualize entrepreneurial opportunities as being both "made" and "found" in and through such interactions. We are sympathetic to the progressive shift in the conceptualization of entrepreneurial agency—from one that considers it to be located in specific individuals to one that considers it to be an outcome of an ecology of interactions between humans and artifacts. Yet there are unaddressed issues pertaining to the location of boundaries that are germane to entrepreneurial opportunities. Boundaries, after all, are not given but, rather, a key ontological variable constituting entrepreneurial agency. As a way to address this issue and add to this dialogue, we propose a "narrative perspective" that is informed by actor-network theory (Callón, 1986; Latour, 2005). Such a perspective subscribes to a relational ontology, one where what is "in" and what is "out" is not given but instead emerges in and through actions and interactions (Garud, Kumaraswamy, & Karnöe, 2010). An additional advantage of taking a narrative perspective is that it endogenizes time (Garud & Gehman, 2012), thereby allowing one to examine issues around temporal agency, a facet that Venkataraman et al. (2012) allude to in their review but leave unexplored. Finally, a narrative perspective emphasizes "meaning making" (e.g., Bruner, 1990) as a core driver of the process and provides yet another vantage point on the nature and scope of entrepreneurial opportunities and agency.